1989
DOI: 10.1111/j.1439-0434.1989.tb04915.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibacterial Activity of Acrophialophora levis Samson and Tariq Mahmood

Abstract: In studies conducted to gain information on the antagonistic potential of Acrophialophora levis, an isolate obtained from the rhizosphere of olive trees in Aegean Region (Turkey) was assayed in vitro for its antibiotic activity against 16 important soil-borne plant pathogenic fungi belonging to Mastigomycotina, Ascomycotina, Basidiomycotina and Deuterornycotina, and six bacteria by using the streak method. The results of this study clearly demonstrated that A. levis exhibited an antagonistic activity against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For example, A. fusispora was effective against F. udum (Rai and Upadhyay, 1983), M. phaseolina (Siddiqui and Mahmood, 1992), F. solani, M. phaseolina, P. aphanidermatum, R. solani and S. rolfsii, and A. porri (Demirci et al, 2011;Abdel-Hafez et al, 2015). Acrophialophora levis was antagonistic against P. debaryanum, P. capsica, S. sclerotiorum, B. cinerea, Gaeomannomyces graminis, and R. solani (Turhan and Grossmann, 1989), and A. jodhpurensis had antagonistic effect against R. solani (Daroodi et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, A. fusispora was effective against F. udum (Rai and Upadhyay, 1983), M. phaseolina (Siddiqui and Mahmood, 1992), F. solani, M. phaseolina, P. aphanidermatum, R. solani and S. rolfsii, and A. porri (Demirci et al, 2011;Abdel-Hafez et al, 2015). Acrophialophora levis was antagonistic against P. debaryanum, P. capsica, S. sclerotiorum, B. cinerea, Gaeomannomyces graminis, and R. solani (Turhan and Grossmann, 1989), and A. jodhpurensis had antagonistic effect against R. solani (Daroodi et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…This fungus is classified in Ascomycota and belongs to the Chaetomiaceae family. The genus Acrophialophora is previously reported as a biocontrol agent against several phytopathogens, such as Pythium aphanidermatum (Sharma et al, 1981;Ramzan et al, 2014), Fusarium udum (Rai and Upadhyay, 1983), Phythium debaryanum, Phytophthora capsica, Sclerotinia sclerotiorum, Botrytis cinerea, Gaeomannomyces graminis, R. solani (Turhan and Grossmann, 1989;Ramzan et al, 2014;Daroodi et al, 2021a), Macrophomina phaseolina (Siddiqui and Mahmood, 1992;Ramzan et al, 2014), Fusarium solani (Ramzan et al, 2014), and Alternaria porri (Abdel-Hafez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in previous studies Acrophialophora sp. was extensively studied for production of industrial enzyme [ 38 43 ] however, no report was present on antibacterial and antioxidant activity. This study reports for the first time, the potential source of anti- S .…”
Section: Discussionmentioning
confidence: 99%
“…Stachybotrys elegans proved to be the most promising among these fungi. Another study conducted by the same laboratory demonstrated the antifungal and antibacterial activity of A. levis, which inhibited all of the 16 important plant pathogenic fungi (Turhan and Grossmann, 1989).…”
Section: Biological Control Agentsmentioning
confidence: 98%